British design 2004-2005 : branding and graphic design, packaging design, new media design, interior, retail and event design, product design. (Amsterdam : Bis, 2004)
British Design 2005 is the second edition of BIS Publishers' cross-section of design studios and creative consultancies in Britain. The changes in the design industry over the last two years is of course reflected in this book: a lot of new names now present themselves for the first time, along with many established firms that are in here again because they experienced the benefits of getting their work out to the (inter)national audience of design buyers who use the book. The goal of this book is simple: it helps clients in their search for the ideal design partner. British Design 2005 provides an instant impression of each participating studio's work - it is a reference tool for whenever professional creative input is needed. To underestimate the power of design as a visual communication interface between user and product would be a grave error in judgment. This is the conclusion of Corinna Dean's article in this book. Look around you and you see a world full of identities, trademarks and other interfaces. It is apparent that the commercial world is aware of the necessity of working with design. The new challenge however, for both clients and designers, is to really differentiate through creativity, to become a first grade version of yourself, rather than a second grade version of somebody else.
Keywords: Groot-Brittannië.; Vormgeving